Comprehensive thermal preference phenotyping in mice using a novel automated circular gradient assay - Touska, Filip; Winter, Zoltán; Mueller, Alexander; Vlachova, Viktorie; Larsen, Jonas; Zimmermann, Katharina (Temperature°, 2016)
Currently available behavioral assays to quantify normal cold sensitivity, cold hypersensitivity and cold hyperalgesia in mice have betimes created conflicting results in the literature. Some only capture a limited spectrum of thermal experiences, others are prone to experimenter bias or are not sensitive enough to detect the contribution of ion channels to cold sensing because in mice smaller alterations in cold nociception do not manifest as frank behavioral changes. To overcome current limitations we have designed a novel device that is automated, provides a high degree of freedom, i.e. thermal choice, and eliminates experimenter bias. The device represents a thermal gradient assay designed as a circular running track. It allows discerning exploratory behavior from thermal selection behavior and provides increased accuracy by providing measured values in duplicate and by removing edge artifacts. Our custom-designed automated offline analysis by a blob detection algorithm is devoid of movement artifacts, removes light reflection artifacts and provides an internal quality control parameter which we validated. The assay delivers discrete information on a large range of parameters extracted from the occupancy of thermally defined zones such as preference temperature and skew of the distribution. We demonstrate that the assay allows increasingly accurate phenotyping of thermal sensitivity in transgenic mice by disclosing yet unrecognized details on the phenotypes of TRPM8-, TRPA1- and TRPM8/A1-deficient mice.